-11/13=x+1/13

Simple and best practice solution for -11/13=x+1/13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11/13=x+1/13 equation:



-11/13=x+1/13
We move all terms to the left:
-11/13-(x+1/13)=0
We add all the numbers together, and all the variables
-(+x+1/13)-11/13=0
We get rid of parentheses
-x-1/13-11/13=0
We multiply all the terms by the denominator
-x*13-1-11=0
We add all the numbers together, and all the variables
-x*13-12=0
Wy multiply elements
-13x-12=0
We move all terms containing x to the left, all other terms to the right
-13x=12
x=12/-13
x=-12/13

See similar equations:

| 6x-31-20x=3-(10-4X) | | 3/10+c=11/15 | | 6-7x+x2=0 | | 6x-31-20x=3-(10-4X0 | | 5x+40=11x-60 | | 11+n/11=2 | | 8h^2+9h-575=0 | | 3(16)+29=x | | 5(16)+23=x | | 4y-7+2y=-3y=-3y-1 | | 5x+4=15+4x | | 7/5+3/5x=38/15+4/3x+1/3 | | 4v+2(8-8v)=40-4v | | 3(16)+2=x | | 2+8y=24 | | 2^(n+4)-2^(n+2)=3 | | 3(p+2)-7=18 | | 9-2x=7x-27 | | 5(v-3)=8v-36 | | 3n+29+5n+23=180 | | 3x-18-(6x-4) = 10+3(2+4x) | | x-x/3=12 | | 2/3=u+3/5 | | 175m-125m+48000=50250-200m | | 3n+29=5n+23 | | 6(x-1)=-14(x-5) | | 1/3m+3−5/6m=−15 | | 4y+7-10=10+3y | | (X^3-9)÷(x-3)=0 | | 2x+15=43-4x | | 4x+8=30+2x | | .75x=34 |

Equations solver categories